A coesão sequencial em textos do gênero carta aberta: proposta de intervenção para o ensino fundamental - Costa, Jediael Ferreira da (2019)
This research study discusses the worry of the Portuguese teachers, mainly with the question of how to make teaching enjoyable and meaningful for the student, so that its purpose goes beyond school approval. In our classroom practice, It was possible to notice that students had some difficulties in recognizing the compositional organization of textual genres, as well as in establishing sequential cohesion. That hamper, in some situations, the continuation of the sense of the text. Therefore, this research has as general objective to investigate the resources of sequential cohesion in the construction and sequencing of the text, about the production of the genre Open Letter, considering the level of adequacy signaled by the student about the organization of the text. Therefore, we selected as specific objectives: to describe the compositional structure of the texts written by 9th-grade students in the Open Letter genre; characterize the compositional structure of the genre; identify the elements of sequential cohesion in the texts produced; characterize the elements of sequential cohesion in the Open Letter genre; to analyze the role of cohesive elements in the construction of the meanings of the text. The theories by Koch and Elias (2006; 2010), Koch (2002; 2011; 2013), Marcuschi (2005; 2008), Antunes (2005; 2009; 2010), Geraldi (2011), among others, have been utilized in the construction of this work. About the methodological aspects, we resort to the qualitative and interpretative approach, based on the studies of Flick (2009), Fonseca (2002), Marconi and Lakatos (2011). This investigation, from the point of view of the research typology, meets the principles of action research, in accordance with the studies by Thiollent (2011), characterized by the intervention of the teacher in the classroom. The research data were generated from the application of a sequence of activities developed based on the modular guidelines of Dolz, Noverraz and Schneuwly (2004), through which students produced an initial version and a final version of the Open Letter. In the initial version, students appropriated some connectors in order to establish the relevant semantic relationships. In the final production, new connectors were identified, providing the expansion of new semantic relations, contributing to the establishment of textual cohesion. Regarding the textual genre, we found that, in general, the students produced texts according to the specifications of the Open Letter. Consequently, objectives were reached once the students produced significant texts through which they were able to contribute to the resolution of situated problems, interacting socially through the written text.